Impacts of Canopy Gap to the Understory Plants Abundance on Stands of Pinus oocarpa Schiede and Agathis alba (Lam.) Foxw. - Danang Wahyu Purnomo; Didi Usmadi; Julisasi Tri Hadiah (Jurnal Ilmu Kehutanan)
Understory plant existed by canopy gap is distinct advantages for the local ecosystem, including the provision of nutrition for the forest stand. The research aimed to identify impacts of canopy gap to the understory plants abundance. Data were collected using line transect method, which a plot (2 m × 2 m) was placed on opposite direction with contour line in Pinus oocarpa stand, Agathis alba stand, and the natural forest as a control. The results showed that diversity of understory in all stands was high, i.e. Diversity Index (H’) of pine stands was 3.19, agathis stands was 3.19, and the natural forest was 3.4. Regression analysis showed a higher value of canopy cover significantly decreased species diversity. Reduction of 100% canopy cover would result in an increase of diversity index of 2.11. Thinning and pruning were required on pine stands in Block 43 Lebak Siu (canopy cover average/ X=0.7) and Block 44 Rangkahan (X=0.65) as well as agathis stands in Block 55 Kompos (X =0.51) and Block 55 Pancuran (X=0.50). Clearing was required to the exotic plants i.e. Clidermia hirta, Disporum uniflorum, and Nephrolepis exaltata to maintain the sustainability of native species.